Catechin-driven dual metabolic modulation enhances docosahexaenoic acid biosynthesis and oxidative stability in Schizochytrium sp - Chengxi Zhang; Zifan Zhang; Yuxuan Chen; Yingfeng Li; Guang Yang; Xiaoman Sun; Wang Ma (Bioresource Technology, 2027)

Engineering Naematelia aurantialba as a Robust Synthetic Biology Chassis: Stable Episomal Vector Construction and Metabolic Optimization for Enhanced Polysaccharide Synthesis - Yuhang Ma; Yingfeng Wang; Ming Zhang; Liang Sun; Rui Wang; Yian Gu; Peng Lei; Hong Xu (Bioresource Technology, 2026)

Hydrophilic PAMAM dendrimer grafted Janus membrane for oil-water emulsion separation - Yunqi Chen; Xiang Wang; Haoyuan Sun; Xinqiang Wang; Baihu Dong; Chaogang Fan; Yingfeng Tu; Shaohui Lin; Qinmin Pan; Xianshe Feng; Flora T.T. Ng (Journal of Environmental Chemical Engineering, 2026)

Dynamic evolution of coal nanopores during CO2 adsorption after progressive immersion-drying damage: An in situ SAXS study - Chengxi Wang; Yixin Zhao; Shuaipeng Zhu; Xiaodong Guo; Yingfeng Sun (Gas Science and Engineering, 2026)

Functional interaction between Bacillus velezensis D103 and maize reveals a microbial mechanism for drought stress mitigation via photosynthesis and sugar metabolism - Yating Zhang; Zhenqiang Feng; Yanling Guo; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Bo Zhang; FangFang Yu; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; et al. (Plant Science, 2026)

Molecular engineering of a dual-functional hyperbranched epoxy with pyrene moieties for high-performance composites with integrated properties - Fengying Zhang; Haiwei Zou; Hongru Zhou; Yingfeng Wen; Xingping Zhou; Yong Wang; Xiaolin Xie (Chemical Engineering Journal, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Separation of vanadium and molybdenum from a sulfuric acid leachate - Bingxu Chen; Chunliu Li; Huaijiang Wang; Ruishu Wang; Yingfeng Cuan; Haojie Meng; Bingwu Chu (Hydrometallurgy, 2026)

Photoresponsive MXene/HKUST-1@CuS antimicrobial nanosheets towards efficient solar-driven water evaporation and biofilm eradication - Yingfeng Wang; Ming Huang; Maoli Yin; Wei Li; Xun Zhang; Xiaojuan Li; Gang Li (Journal of Environmental Chemical Engineering, 2026)

Interpretable multi-task dual-attention model for forecasting heating load and supply water temperature in district heating systems - Yingfeng Lin; Chun-E Huang; Chunwang Li; Hui Wang; Chuanzhao Zhang (Energy and Buildings, 2026)

Prenatal exposure to mixtures of metals and metalloids and risk of spontaneous preterm birth: Critical exposure windows and susceptibility factors - Ruiwei Xu; Yi Zhang; Yingfeng Gao; Le Zhang; Bin Wang; Xiaoqian Jia; Min Xu; Zhiwen Li; Jicheng Gong (Journal of Hazardous Materials, 2026)

Multifunctional carbon nanowebs for solar-driven desalination and water purification with integrated Photothermal, antibacterial, and adsorptive capabilities - Bing Gao; Zhi Liu; Soon Huat Tan; Jianghui Zhao; Yingfeng Wang; Siew Chun Low (Desalination, 2026)

Bacillus velezensis D103 enhances maize drought tolerance via ROS-scavenging and phenylpropanoid pathway activation - Yating Zhang; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Fangfang Yu; Bo Zhang; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; Ning Zhang; Bingxue Li (Plant Cell Reports, 2026)

Long-term exposure to ultrafine particles accelerates biological aging and increases respiratory vulnerability in COPD - Yingfeng Gao; Xin Meng; Yi Zhang; Qiaoyi Hua; Ruiwei Xu; Huixia Liu; Seokho Choi; Haoyang Yao; Qianli Dong; Qi Jia; Haixia Jiang; Lijuan Wei; et al. (Journal of Hazardous Materials, 2025)

Prediction of critical volatile organic compounds and identification of flavor intensity in Gastrodia elata under different preparation methods based on NIR and FTIR feature variables - Yingfeng Zhong; Jieqing Li; Honggao Liu; Yuanzhong Wang (Food Research International, 2025)

Tanshinone IIA ameliorates pancreatic injury in type 2 diabetic mice by modulating inflammation and endoplasmic reticulum stress via the IL-6/JAK2/STAT3 pathway - Yingfeng Li; Desheng Wang; Yuhang Liu; Chenyang Liu; Meixi Chen; Jingqi Li; Zunqiu Wu; Ning Wu (Functional & Integrative Genomics, 2025)

What is the relationship between urban heat island (UHI) effect and urban surface parameter (USP) at micro-scale? A case study in Gulangyu, China - Yuan Li; Yingfeng Wang; Mengsheng Yang; Yanan Du; Jingge Liu (Sustainable Cities and Society, 2025)

Liquid-mediated dense integration of graphene oxide/N-halamine aerogel microspheres with exceptional UV stability and antimicrobial activity for sewage purification - Nengyu Pan; Xiaoxing Xu; Yuting Xue; Wei Wang; Yingfeng Wang (Chemical Engineering Journal, 2025)

Corrigendum to “Novel energy management strategy based on expert-guidance DDPG for hybrid electric combine harvester in the journal computers and electronics in agriculture”. [Comput. Electron. Agr. 236 (2025) 110475] - Feng Wang; Wenbin Xie; Xiaoyuan Zhu; Yingfeng Cai (Computers and Electronics in Agriculture, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Carboxymethyl chitosan and poly-γ-glutamic acid-based gastroretentive sponge with high swelling and mechanical stability for targeted eradication of Helicobacter pylori - Xinyuan Zhang; Pei Xie; Yongkang Lai; Jiulong Zhao; Qiuping Gu; Yingfeng Wei; Zheng Chen; Liang Zhang; Shige Wang; Hongxin Sun; Chunping Zhu (Carbohydrate Polymers, 2025)

Novel energy management strategy based on expert-guidance DDPG for hybrid electric combine harvester - Feng Wang; Wenbin Xie; Xiaoyuan Zhu; Yingfeng Cai (Computers and Electronics in Agriculture, 2025)

Seismic Prediction of Shallow Unconsolidated Sand in Deepwater Areas - Jiale Chen; Yingfeng Xie; Tong Wang; Haoyi Zhou; Zhen Zhang; Yonghang Li; Shi Zhang; Wei Deng (Journal of Marine Science and Engineering, 2025)
Recently, shallow gas fields and hydrate-bearing sand in the deepwater area of the northern South China Sea have been successively discovered, and the accurate prediction of shallow sands is an important foundation. However, most of the current prediction methods are mainly for deep oil and gas reservoirs. Compared with those reservoirs with high degree of consolidation, shallow sandy reservoirs are loose and unconsolidated, whose geophysical characteristics are not well understood. This paper analyzes the logging data of shallow sandy reservoirs recovered in the South China Sea recently, which show that the sand content has a significant influence on Young’s modulus and Poisson’s ratio of the sediments. Therefore, this paper firstly constructs a new petrophysical model of unconsolidated strata targeting sandy content and qualitatively links the mineral composition and the elastic parameters of the shallow marine sediments and defines a new indicator for sandy content: the modified brittleness index (MBI). The effectiveness of MBI in predicting sandy content is then verified by measured well data. Based on pre-stack seismic inversion, the MBI is then inverted, which will identify the sandy deposits. The method proposed provides technical support for the subsequent shallow gas and hydrate exploration in the South China Sea.

Effect of (−)-epigallocatechin gallate palmitate complexation under mild temperature on the structure and nutritional functions of porous rice starch - Hai He; Qi He; Yugang Zhang; Jia Sun; Yingfeng Tu; Hongwei Wang; Fang Qin; Kun Liu (Food Chemistry, 2025)

Targeted isolation of cellulose nanofibers of specific length distributions from potato residue - Yingfeng Wang; Timo Pääkkönen; Laleh Solhi; Neptun Yousefi; Eero Kontturi (Carbohydrate Polymers, 2025)

Exploring the Dynamic Evolution of Shallow and Deep Coal Nanopore Structures Under Acidic Fracturing Fluids Using Synchrotron Radiation Small-Angle X-Ray Scattering - Yingfeng Sun; Shuaipeng Zhu; Hui Wang; Yixin Zhao; Fei Xie; Ping Chen; Changjiang Ji; Zhaoying Chen; Qifei Wang (Natural Resources Research, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Mechanism of anti-hepatitis potential of Tagetes erecta L.: UPLC-Q-TOF-M S/MS, network pharmacology, molecular docking and in vitro experimental validation - Jiangning Peng; Zhenxia Zhao; Zhiqian Yuan; Yingfeng Du; Hong Wang; Yunhe Lian; Xinyi Yang; Hui Li (Next Research, 2025)

How to classify microclimates more validly and finely? A novel method for mapping local climate zone (LCZ) on micro-scales - Mengsheng Yang; Yuan Li; Yanan Du; Yingfeng Wang; Jingge Liu; Lijuan Yang; Jingxiong Huang (Sustainable Cities and Society, 2025)

VNI-Net: Vector neurons-based rotation-invariant descriptor for LiDAR place recognition - Gengxuan Tian; Junqiao Zhao; Yingfeng Cai; Fenglin Zhang; Xufei Wang; Chen Ye; Sisi Zlatanova; Tiantian Feng (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Enabling (De)bonding on-demand with optically switchable pressure sensitive adhesive tape via photodimerization - Gang Wang; Xinrong Huang; Zhengxiang Zhou; Yi Zhang; Yingfeng Yu (Chemical Engineering Journal, 2024)

Characterization of a novel multifunctional β-glucosidase/xylanase/feruloyl esterase and its effects on improving the quality of Longjing tea - Hongling Wang; Xianghui Qi; Song Gao; Guoshi Kan; Lkhagvasuren Damdindorj; Yingfeng An; Fuping Lu (Food Chemistry, 2024)

What is the outdoor thermal comfort (OTC) threshold in Gulangyu, China: An empirical study - Mengsheng Yang; Yuan Li; Yanan Du; Yingfeng Wang; Wenyi Fei; Jingxiong Huang; Jiaqi Liang (Urban Climate, 2024)

Achieving sustainable and highly efficient wood bonding through synergistic plant root-driven penetration mode with a hyperactive interface - Xiaoqian Bi; Yuan Zhang; Ping Li; Yan Wang; Yiqiang Wu; Yingfeng Zuo (Chemical Engineering Journal, 2024)

Large language models for diabetes care: Potentials and prospects - Bin Sheng; Zhouyu Guan; Lee-Ling Lim; Zehua Jiang; Nestoras Mathioudakis; Jiajia Li; Ruhan Liu; Yuqian Bao; Yong Mong Bee; Ya-Xing Wang; Yingfeng Zheng; Gavin Siew Wei Tan; et al. (Science Bulletin, 2024)

Genomic sequencing revealed recombination event between clade 1 and clade 2 occurs in circulating varicella-zoster virus in China - Jia Li; Dan Wang; Libin Qi; Yuewu Yang; Jiawei Pei; Yangchao Dong; Yuan Wang; Min Yao; Fanglin Zhang; Yingfeng Lei; Linfeng Cheng; Wei Ye (Brazilian Journal of Microbiology, 2024)

Study on CO source identification and spontaneous combustion warning concentration in the return corner of working face in shallow buried coal seam - Chengxi Wang; Po Hu; Yingfeng Sun; Chunran Yang (Environmental Science and Pollution Research, 2024)

Dual drug-loaded calabash-like nanomotor as an active therapeutic for enhanced chemo-photothermal therapy of orthotopic glioblastoma - Huaan Li; Xiaoting Zhang; Jiajun Miao; Zhengyu Shi; Ziqi Li; Minjun Wen; Limeng Wang; Jiayuan Liang; Junbin Gao; Yicheng Ye; Hao Tian; Fei Peng; et al. (Chemical Engineering Journal, 2023)

SVMD coupled with dual-threshold criteria of correlation coefficient: A self-adaptive denoising method for ship-radiated noise signal - Haomiao Ma; Yingfeng Xu; Jianye Wang; Mengmeng Song; Shenglun Zhang (Ocean Engineering, 2023)

Degradation of cellulose polymorphs into glucose by HCl gas with simultaneous suppression of oxidative discoloration - Yingfeng Wang; Timo Pääkkönen; Kim Miikki; Ndegwa H. Maina; Kaarlo Nieminen; Aleksi Zitting; Paavo Penttilä; Han Tao; Eero Kontturi (Carbohydrate Polymers, 2023)

Study on failure characteristics and in situ stress inversion of brittle shale under complex loading - Houbin Liu; Shuai Cui; Yingfeng Meng; Jiajun Wang; Bin Lv (Arabian Journal of Geosciences, 2022)

Nature restoration shifts the abundance and structure of soil nematode communities in subtropical forests - Jianqing Wang; Yingfeng Zheng; Xiuzhen Shi; Shu Kee Lam; Manuel Esteban Lucas-Borja; Zhiqun Huang (Plant and Soil, 2022)

Changes in Copper, Zinc, Arsenic, Mercury, and Lead Concentrations in Rat Biofluids and Tissues Induced by the “Renqing Changjue” Pill, a Traditional Tibetan Medicine - Lan Zhang; Caidan Rezeng; Yingfeng Wang; Zhongfeng Li (Biological Trace Element Research, 2021)

Correction to: Bibliometrics and visualization analysis regarding research on the development of microplastics - Mengjiao Zhou; Rou Wang; Shuiping Cheng; Yingfeng Xu; Sha Luo; Yi Zhang; Lingwei Kong (Environmental Science and Pollution Research, 2021)

Bibliometrics and visualization analysis regarding research on the development of microplastics - Mengjiao Zhou; Rou Wang; Shuiping Cheng; Yingfeng Xu; Sha Luo; Yi Zhang; Lingwei Kong (Environmental Science and Pollution Research, 2021)

Quantitative study on the fate of antibiotic emissions in China - Shuxin Chen; Jing Wang; Huajun Feng; Dongsheng Shen; Shichong He; Yingfeng Xu (Environmental Geochemistry and Health, 2020)

Study of failure mechanism of bottom-hole rock mass approaching a gas-fractured zone during nitrogen drilling - Luo Chengbo; Jiang Zujun; Li Gao; He Long; Ou Biao; Meng Yingfeng; Xiao Guoyi; Yan Yancheng; Wang Xiyong (Arabian Journal of Geosciences, 2020)

Clinical characteristic of 15 cases of cryptococcal meningitis treated with Ommaya reservoir - Yingfeng Wan; Xinwei Li; Yirong Wang; Yunsong Yu; Shuxu Yang (Acta Neurologica Belgica, 2020)

Functional Metagenomic Technologies for the Discovery of Novel Enzymes for Biomass Degradation and Biofuel Production - Hongling Wang; Darren J. Hart; Yingfeng An (BioEnergy Research, 2019)

Isolation and Analysis of Salt Response of Lactobacillus plantarum FS5-5 from Dajiang - Xuefei Song; Qianqian Wang; Xin Xu; Jingwei Lin; Xiaorui Wang; Yating Xue; Rina Wu; Yingfeng An (Indian Journal of Microbiology, 2016)

Clinical characteristics of 15 cases of chronic subdural hematomas due to spontaneous intracranial hypotension with spinal cerebrospinal fluid leak - Yingfeng Wan; Jixi Xie; Dajiang Xie; Zhaoliang Xue; Yirong Wang; Shuxu Yang (Acta Neurologica Belgica, 2016)

Putrescine protects hulless barley from damage due to UV-B stress via H2S- and H2O2-mediated signaling pathways - Qien Li; Zhaofeng Wang; Yanning Zhao; Xiaochen Zhang; Shuaijun Zhang; Letao Bo; Yao Wang; Yingfeng Ding; Lizhe An (Plant Cell Reports, 2016)

Effect of CDKN2A/B rs4977756 polymorphism on glioma risk: a meta-analysis of 16 studies including 24077 participants - Xuchen Qi; Yingfeng Wan; Qitao Zhan; Shuxu Yang; Yirong Wang; Xiujun Cai (Mammalian Genome, 2016)

Cystic olfactory ensheathing cell tumor: a case report - Xuchen Qi; Yingfeng Wan; Qingfeng Yan; Yirong Wang; Shuxu Yang (Acta Neurologica Belgica, 2015)

Peroxisome proliferator-activated receptor γ inhibits pulmonary hypertension targeting store-operated calcium entry - Yingfeng Wang; Wenju Lu; Kai Yang; Yan Wang; Jie Zhang; Jing Jia; Xin Yun; Lichun Tian; Yuqin Chen; Qian Jiang; Bo Zhang; Xiuqing Chen; et al. (Journal of Molecular Medicine, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

15 N ‐ and 2 H proteomic stable isotope probing links nitrogen flow to archaeal heterotrophic activity - Nicholas B. Justice; Zhou Li; Yingfeng Wang; Susan E. Spaudling; Annika C. Mosier; Robert L. Hettich; Chongle Pan; Jillian F. Banfield (Environmental Microbiology, 2014)
Summary Understanding how individual species contribute to nutrient transformations in a microbial community is critical to prediction of overall ecosystem function. We conducted microcosm experiments in which floating acid mine drainage ( AMD ) microbial biofilms were submerged – recapitulating the final stage in a natural biofilm life cycle. Biofilms were amended with either 15 NH 4 + or deuterium oxide ( 2 H 2 O ) and proteomic stable isotope probing ( SIP ) was used to track the extent to which different members of the community used these molecules in protein synthesis across anaerobic iron‐reducing, aerobic iron‐reducing and aerobic iron‐oxidizing environments. S ulfobacillus spp. synthesized 15 N ‐enriched protein almost exclusively under iron‐reducing conditions whereas the L eptospirillum spp. synthesized 15 N ‐enriched protein in all conditions. There were relatively few 15 N ‐enriched archaeal proteins, and all showed low atom% enrichment, consistent with A rchaea synthesizing protein using the predominantly 14 N biomass derived from recycled biomolecules. In parallel experiments using 2 H 2 O , extensive archaeal protein synthesis was detected in all conditions. In contrast, the bacterial species showed little protein synthesis using 2 H 2 O . The nearly exclusive ability of A rchaea to synthesize proteins using 2 H 2 O may be due to archaeal heterotrophy, whereby A rchaea offset deleterious effects of 2 H by accessing 1 H generated by respiration of organic compounds.

Cloning and Tissue-Specific Expression of Predicted Pisum sativum Actin Isoform PEAc14-1 - Shaobin Zhang; Fangsheng Cheng; Can Wang; Lijun Zhang; Yingfeng An (Biochemical Genetics, 2013)